Design and Optimization of a Surface-Mounted Permanent-Magnet Linear Synchronous Motor with Maxwell ANSYS - Jamal Abdul-Kareem Mohammed (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
Linear motor offers several features in many applications that require linear motion. Nevertheless, the presence of cogging force can deteriorate the thrust of a permanent magnet linear motor. Using several methodologies, a design of synchronous single sided linear iron-core motor was proposed. According to exact formulas with surface-mounted magnets and concentrated winding specification, which are relying on geometrical parameters. Two-dimensional performance analysis of the designed model and its multi-objective optimization were accomplished as a method to reduce the motor cogging force using MAXWELL ANSYS. The optimum model design results showed that the maximum force ripple was approximatrly reduced by 81.24%compared to the original model with a smaller ripple coefficient of 0.22. Likewise, the model was redesigned taking into consideration two cases; laminated core and solid core. It was found that the error between the analytical and numerical results of the output force did not exceed 0.0967%.